2013
DOI: 10.1371/journal.pone.0076688
|View full text |Cite
|
Sign up to set email alerts
|

Are Organic Falls Bridging Reduced Environments in the Deep Sea? - Results from Colonization Experiments in the Gulf of Cádiz

Abstract: Organic falls create localised patches of organic enrichment and disturbance where enhanced degradation is mediated by diversified microbial assemblages and specialized fauna. The view of organic falls as “stepping stones” for the colonization of deep-sea reducing environments has been often loosely used, but much remains to be proven concerning their capability to bridge dispersal among such environments. Aiming the clarification of this issue, we used an experimental approach to answer the following question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 71 publications
3
38
0
Order By: Relevance
“…Details on the environmental setting of the latter two mud volcanoes can be found in Cunha et al (2013a). An account of the colonization experiments and a brief description of Darwin MV are provided by Cunha et al (2013b). Whenever possible the specimens were sorted on board and preserved in 96% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Details on the environmental setting of the latter two mud volcanoes can be found in Cunha et al (2013a). An account of the colonization experiments and a brief description of Darwin MV are provided by Cunha et al (2013b). Whenever possible the specimens were sorted on board and preserved in 96% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, seven are also known from wood-falls or from nutrient-rich substrates of anthropogenic origin, and, therefore, the genus is considered to be composed of organic-enriched generalists and not whale-fall specialists. Organic falls may be more common in the deep-sea than initially thought (Cunha et al, 2013;Higgs, Gates, & Jones, 2014;Stockton & DeLaca, 1982), shortening the distances between patches of suitable habitats and making them reachable by taxa with relatively low dispersal capabilities. It has been shown that even small volumes of organic material allow growth to reproductive maturity and it is likely that organic-fall specialists and opportunists, such as Ophryotrocha species, use these as dispersal stepping-stones (Cunha et al, 2013).…”
Section: Research Articlementioning
confidence: 96%
“…spatula from the Haakon Mosby Mud Volcano in the Norwegian margin (Paxton & Morineaux, 2009). Several Ophryotrocha species were also found in colonization experiments using plant material but remain undescribed (Cunha et al, 2013). The presence of five different congeners emphasizes the importance of Ophryotrocha in the degradation of organic matter in the deep Atlantic Ocean.…”
mentioning
confidence: 99%
“…However, the capability of organic falls to bridge dispersal among such assemblages and so ensure present‐day population connectivity of their species is still being debated (Cunha et al . ). Colonization and population dynamics of discrete resource patches, varying in time and space, are far from being understood.…”
Section: Introductionmentioning
confidence: 97%